AHP 28: Review: Trade and Society along the Ancient Silk Road - Bina, Sengar (Asian Highlands Perspectives, 2018)
Ladakh in the twenty-first century is well known as a religious and touristic destination as well as an Indian border territory with Kargil and Siachin - significant military posts. In contrast, the commercial role of Ladakh in trade within the Himalayan region and along the Silk Route is less explored. In this well-researched book, Fewkes presents various components of Ladakh's ethno-history of trade. She focuses on Ladakh since the eighteenth century and its status as a trade center in pre-independence India and thereafter. Its lost legacy of trade and commerce and associated facets of its culture, history, and future challenges are presented compactly in less than 200 pages. ...